15-Deoxy-Δ(12,14)-prostaglandin J(2): The endogenous electrophile that induces neuronal apoptosis - Kondo, Mitsuhiro (The National Academy of Sciences, 2002)
Prostaglandin D(2) (PGD(2)), a major cyclooxygenase product in a variety of tissues and cells, readily undergoes dehydration to yield the bioactive cyclopentenone-type PGs of the J(2)-series, such as 15-deoxy-Δ(12,14)-PGJ(2) (15d-PGJ(2)). The observation that the level of 15d-PGJ(2) increased in the tissue cells from patients with sporadic amyotrophic lateral sclerosis suggested that the formation of 15d-PGJ(2) may be closely associated with neuronal cell death during chronic inflammatory processes. In vitro experiments using SH-SY5Y human neuroblastoma cells revealed that 15d-PGJ(2) induced apoptotic cell death. An oligonucleotide microarray analysis demonstrated that, in addition to the heat shock-responsive and redox-responsive genes, the p53-responsive genes, such as gadd45, cyclin G1, and cathepsin D, were significantly up-regulated in the cells treated with 15d-PGJ(2). Indeed, the 15d-PGJ(2) induced accumulation and phosphorylation of p53, which was accompanied by a preferential redistribution of the p53 protein in the nuclei of the cells and by a time-dependent increase in p53 DNA binding activity, suggesting that p53 accumulated in response to the treatment with 15d-PGJ(2) was functional. The 15d-PGJ(2)-induced accumulation of p53 resulted in the activation of a death-inducing caspase cascade mediated by Fas and the Fas ligand.